Retroviral gene therapy for X-linked chronic granulomatous disease: results from phase I/II trial - Kang, Hyoung Jin; Bartholomä, Cynthia C.; Paruzynski, Anna; Arens, Anne; Kim, Sujeong; Yu, Seung Shin; Hong, Youngtae; Joo, Chang-Wan; Yoon, Nam-Kyung; Rhim, Jung-Woo; Kim, Joong Gon; Kalle, Christof von; et al. (Molecular therapy, 2011)
X-linked chronic granulomatous disease (CGD) is an inherited immunodeficiency caused by a defect in the gp91phox gene. In an effort to treat X-CGD, we investigated the safety and efficacy of gene therapy using a retroviral vector, MT-gp91. Two X-CGD patients received autologous CD34+ cells transduced with MT-gp91 after a conditioning regimen consisting of fludarabine and busulfan. The level of gene-marked cells was highest at day 21 (8.3 and 11.7% in peripheral blood cells) but decreased to 0.08 and 0.5%, respectively, 3 years after gene transfer. The level of functionally corrected cells, as determined by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase assay, reached a peak at day 17 (6.5% patient 1 (P1) and 14.3% patient 2 (P2) of total granulocytes) and declined to 0.05% (P1) and 0.21% (P2), 3 years later. Some retroviral vectors were found to have integrated within or close to the proto-oncogenes MDS1-EVI1, PRDM16, and CCND2; however, no abnormal cell expansion or related hematological malignancy was observed. Overall, the gene transfer procedure did not produce any serious adverse effects and was able to convert a significant fraction of blood cells to biologically functional cells, albeit for a short period of time.
Gesehen am 11.07.2022